Pediatric malignancies in neurofibromatosis type 1: A population‐based cohort study - Peltonen S; Kallionpää RA; Rantanen M; Uusitalo E; Pöyhönen M; Lähteenmäki PM; Pitkäniemi J; Peltonen J (Wiley, 2022)
Neurofibromatosis type 1 (NF1) is a cancer predisposition syndrome with an incidence of 1:2,000. Patients with NF1 have an increased cancer risk and mortality, but there are no population‐based cohort studies specifically investigating the risk of childhood malignancies. We used the Finnish NF1 cohort to analyze the incidence, risk and prognosis of malignancies in NF1 patients <20 years of age. Persons born in 1987–2011 were included, and 524 persons were followed through the files of the Finnish Cancer Registry from birth up to age 20 years. This amounted to 8,376 person years. Fifty‐three patients had cancer <20 years of age, yielding a standardized incidence ratio (SIR) of 35.6. The most frequent location of pediatric cancers was the central nervous system (CNS); there were 45 cases and the SIR was 115.7. Exclusion of 22 optic pathway gliomas (OPGs) gave an SIR of 59.1 for the CNS and 21.6 for all cancers. There were nine malignant peripheral nerve sheath tumors (MPNSTs); their cumulative risk was 2.7% by age 20. No cases of leukemia were observed. NF1 patients showed considerable excess mortality with a standardized mortality ratio (SMR) of 73.1. The survival of NF1 patients with CNS tumors other than OPGs did not differ from that of non‐NF1 controls (HR 0.64, 95% CI 0.23 to 1.76). In conclusion, brain tumors in childhood and MPNSTs in adolescence are malignancies of major concern in patients with NF1. The risk for myeloid malignancies may not be as high as suggested in the literature.